Characterizing Adversity of Lysosomal Accumulation in Nonclinical Toxicity Studies: Results from the 5th ESTP International Expert Workshop. (February 2018) - Lenz, B.; Braendli-Baiocco, A.; Engelhardt, J.; Fant, P.; Fischer, H.; Francke, S.; Fukuda, R.; Gröters, S.; Harada, T.; Harleman, H.; Kaufmann, W.; Kustermann, S.; et al.
Lysosomes have a central role in cellular catabolism, trafficking, and processing of foreign particles. Accumulation of endogenous and exogenous materials in lysosomes represents a common finding in nonclinical toxicity studies. Histologically, these accumulations often lack distinctive features indicative of lysosomal or cellular dysfunction, making it difficult to consistently interpret and assign adverse dose levels. To help address this issue, the European Society of Toxicologic Pathology organized a workshop where representative types of lysosomal accumulation induced by pharmaceuticals and environmental chemicals were presented and discussed. The expert working group agreed that the diversity of lysosomal accumulations requires a case-by-case weight-of-evidence approach and outlined several factors to consider in the adversity assessment, including location and type of cell affected, lysosomal contents, severity of the accumulation, and related pathological effects as evidence of cellular or organ dysfunction. Lysosomal accumulations associated with cytotoxicity, inflammation, or fibrosis were generally considered to be adverse, while those found in isolation (without morphologic or functional consequences) were not. Workshop examples highlighted the importance of thoroughly characterizing the biological context of lysosomal effects, including mechanistic data and functional in vitro readouts if available. The information provided here should facilitate greater consistency and transparency in the interpretation of lysosomal effects.